Reduced Salience and Enhanced Central Executive Connectivity Following PTSD Treatment. (April 2019) - Abdallah, Chadi G.; Averill, Christopher L.; Ramage, Amy E.; Averill, Lynnette A.; Alkin, Evelyn; Nemati, Samaneh; Krystal, John H.; Roache, John D.; A. Resick, Patricia; Young-McCaughan, Stacey; Peterson, Alan L.; Fox, Peter; et al.
Background: In soldiers with posttraumatic stress disorder, symptom provocation was found to induce increased connectivity within the salience network, as measured by functional magnetic resonance imaging and global brain connectivity with global signal regression (GBCr). However, it is unknown whether these GBCr disturbances would normalize following effective posttraumatic stress disorder treatment. Methods: Sixty-nine US Army soldiers with (n = 42) and without posttraumatic stress disorder (n = 27) completed functional magnetic resonance imaging at rest and during symptom provocation using subject-specific script imagery. Then, participants with posttraumatic stress disorder received six weeks (12 sessions) of group cognitive processing therapy or present-centered therapy. At week 8, all participants repeated the functional magnetic resonance imaging scans. The primary analysis used a region-of-interest approach to determine the effect of treatment on salience GBCr. A secondary analysis was conducted to explore the pattern of GBCr alterations posttreatment in posttraumatic stress disorder participants compared to controls. Results: Over the treatment period, present-centered therapy significantly reduced salience GBCr ( p  = .02). Compared to controls, salience GBCr was high pretreatment (present-centered therapy, p  = .01; cognitive processing therapy, p  = .03) and normalized post-present-centered therapy ( p  = .53) but not postcognitive processing therapy ( p  = .006). Whole-brain secondary analysis found high GBCr within the central executive network in posttraumatic stress disorder participants compared to controls. Post hoc exploratory analyses showed significant increases in executive GBCr following cognitive processing therapy treatment ( p  = .01). Conclusion: The results support previous models relating cognitive processing therapy to central executive network and enhanced cognitive control while unraveling a previously unknown neurobiological mechanism of present-centered therapy treatment, demonstrating treatment-specific reduction in salience connectivity during trauma recollection.